2016
DOI: 10.1074/jbc.m116.752501
|View full text |Cite
|
Sign up to set email alerts
|

An Intronic Enhancer Element Regulates Angiotensin II Type 2 Receptor Expression during Satellite Cell Differentiation, and Its Activity Is Suppressed in Congestive Heart Failure

Abstract: Patients with advanced congestive heart failure (CHF) or chronic kidney disease often have increased angiotensin II (Ang II) levels and cachexia. We previously demonstrated that Ang II, via its type 1 receptor, causes muscle protein breakdown and apoptosis and inhibits satellite cell (SC) proliferation and muscle regeneration, likely contributing to cachexia in CHF and chronic kidney disease. In contrast, Ang II, via its type 2 receptor (AT2R) expression, is robustly induced during SC differentiation, and it p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
11
0
2
Order By: Relevance
“…Though the beneficial effect of AT1R is well established in treating HTN, HF, atherosclerosis, and aortic aneurysms, the beneficial effect of AT2R is under investigation [133–134]. The beneficial role of the AT2R agonist, Compound 21, in diabetes-associated atherosclerosis [135] and increased AT2R expression by targeting intron 2 enhancer element to increase satellite cell proliferation and potentiating skeletal muscle regenerative capacity in CHF patient has been discussed [136]. However, the protective role of AT2R, the underlying mechanism and interaction with vitamin D levels in CVD warrant further investigation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Though the beneficial effect of AT1R is well established in treating HTN, HF, atherosclerosis, and aortic aneurysms, the beneficial effect of AT2R is under investigation [133–134]. The beneficial role of the AT2R agonist, Compound 21, in diabetes-associated atherosclerosis [135] and increased AT2R expression by targeting intron 2 enhancer element to increase satellite cell proliferation and potentiating skeletal muscle regenerative capacity in CHF patient has been discussed [136]. However, the protective role of AT2R, the underlying mechanism and interaction with vitamin D levels in CVD warrant further investigation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recently, Yoshida et al . showed that angiotensin type 1 and 2 receptors (AT1R, AT2R) regulate different stages of satellite cell proliferation and activation (15**). In a mouse model of CHF, there was a marked reduction in muscle regeneration that was associated with attenuated AT2R expression (15**).…”
Section: Satellite Cell Alterations During Chronic and Acute Illnessmentioning
confidence: 99%
“…showed that angiotensin type 1 and 2 receptors (AT1R, AT2R) regulate different stages of satellite cell proliferation and activation (15**). In a mouse model of CHF, there was a marked reduction in muscle regeneration that was associated with attenuated AT2R expression (15**). Eloquent promoter reporter analysis experiments identified intron 2 of AT2R as a transcriptional enhancer element that promotes satellite cell differentiation.…”
Section: Satellite Cell Alterations During Chronic and Acute Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Повыше-ние уровня A-II (циркулирующего, а также локальная концентрация A-II в узловом ганглии) наблюдается очень часто у пациентов с CH или хронической бо лезнью почек [6], при этом, A-II через рецептор 1 типа вызывает разрушение и апоптоз мышечного белка и ингибирует пролиферацию и регенерацию клеток-сателлитов, что, вероятно, способствует кахек-сии при ХСН и хронических заболеваниях почек. Напротив, экспрессия рецептора типа 2 (AT2R) инду-цируется во время дифференцировки клеток-сателли-тов и это потенцирует регенерацию мышц [7].…”
Section: нейрогуморальный дисбаланс при хронической сердечной недостаunclassified